Qualitative Inquiry on Understanding Barangay Governance Through Resident Lenses in Tudela, Misamis Occidental - Tamayo, Jinel V.; Buaquiña, Janine; Tibor, Catherine P.; Egam, Kim John E.; Datwin, Bengie S. (Future Science / FSH-PH Publications, 2025)
This study aimed to explore the problems encountered by residents of Centro Napu, Tudela, Misamis Occidental in relation to the services provided by their barangay. It also sought to gather suggestions from the community to improve these services. A descriptive qualitative research design was employed, involving 18 residents as participants. Data were collected through a structured interview guide, allowing in-depth responses. The findings revealed several challenges faced by the community, including ineffective waste disposal, poor emergency response, weak enforcement of peace and order, inadequate infrastructure maintenance, inconsistent health services, unequal educational support, and inefficient water supply management. In response, residents recommended that barangay officials may practice active listening, conduct proper deliberations before taking action, coordinate with the local government for financial support, and ensure fairness in service delivery. The study emphasized the need for responsive governance at the barangay level and emphasizes the importance of community involvement in addressing local issues as these can build more resilient and inclusive service systems that better meet the needs of their constituents.